2015
DOI: 10.1590/s1808-185120151402142338
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of pedicle screws in adolescent idiopathic scoliosis using electromyography

Abstract: <sec><title>OBJECTIVE:</title><p> To analyze the occurrence of poor positioning of pedicle screws inserted with the aid of intraoperative electromyographic stimulation in the treatment of Adolescent Idiopathic Scoliosis (AIS).</p></sec><sec><title>METHODS:</title><p> This is a prospective observational study including all patients undergoing surgical treatment for AIS, between March and December 2013 at a single institution. All procedures were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…On the LILACS database, with the use of the narrow term intraoperative neurophysiological monitoring, we found 13 articles, but only 9 were related to spinal surgery. [36][37][38][39][40][41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the LILACS database, with the use of the narrow term intraoperative neurophysiological monitoring, we found 13 articles, but only 9 were related to spinal surgery. [36][37][38][39][40][41][42][43][44]…”
Section: Resultsmentioning
confidence: 99%
“…In scoliosis correction surgeries, as there is a high number of levels, there is a real risk of occurrence of poor positioning of the pedicle screws inserted, even with the aid of intraoperative electromyographic stimulation. 36 Kobayashi et al 23 studied the characteristics of cases with intraoperative transcranial motor-evoked potential waveform deterioration (defined as a decrease in intraoperative amplitude 70% of the control waveform) during posterior corrective fusion for adolescent idiopathic scoliosis. Waveform deterioration commonly occurred during rotation maneuvers and more frequently in patients with a larger preoperative Cobb angle.…”
Section: Posterior Fusionmentioning
confidence: 99%
“…A cadaveric study done by Agarwal et al found the sensitivity and specificity of postoperative CT scans to pick up pedicle screw breach was 91.52% and 95.02% respectively [ 35 ]. However, not all patients with pedicle breaches present with neurological deficits [ 36 39 ]. Lotfinia et al reported that nerve root injury with radicular pain and/or neurological deficits was observed only in 15.1% patients with mal-positioned screws [ 12 ].…”
Section: Discussionmentioning
confidence: 99%